2017
DOI: 10.1063/1.4972259
|View full text |Cite
|
Sign up to set email alerts
|

Initial mechanisms for the unimolecular decomposition of electronically excited bisfuroxan based energetic materials

Abstract: Unimolecular decomposition of energetic molecules, 3,3'-diamino-4,4'-bisfuroxan (labeled as A) and 4,4'-diamino-3,3'-bisfuroxan (labeled as B), has been explored via 226/236 nm single photon laser excitation/decomposition. These two energetic molecules, subsequent to UV excitation, create NO as an initial decomposition product at the nanosecond excitation energies (5.0-5.5 eV) with warm vibrational temperature (1170 ± 50 K for A, 1400 ± 50 K for B) and cold rotational temperature (<55 K). Initial decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The similar situation also appeared in the studies of thermal decomposition of a similar structure to DNTF. 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…The similar situation also appeared in the studies of thermal decomposition of a similar structure to DNTF. 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the revealed mechanism can provide a hand to the design of new energetic materials [23,24]. Therefore, unimolecular results represent a reasonable approximation to the primary, initial behavior for the decomposition of energetic molecules in general condensed phase materials [25].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nitro groups significantly changes the photochemical and photophysical behavior of molecules and affect the stability and sensitivity of energetic molecules [ 4 , 5 , 6 ]. Recent literature shows [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] excited energetic molecules deactivated from the S 1 excited state to the S 0 ground state through a conical intersection (CI). Experimental and theoretical studies by Bernstein and coworkers [ 6 ] found that the conical intersection plays an important role in the non-adiabatic decay of the energetic molecule dimethylnitramine (DMNA).…”
Section: Introductionmentioning
confidence: 99%
“…This isomerization process was predicted to take place through a “loose transition state-like geometry”. Bernstein’s group studied the non-adiabatic transitions of many energetic molecules [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and found that their (S 1 /S 0 ) CI are similar in structure. Soto, Arenas and collaborators [ 15 , 16 , 17 ] used the complete active space with second-order perturbation theory (CASPT2) to predict NO 2 –ONO isomerization in nitramide molecules through a (S 1 /S 0 ) CI ; a similar CI structure in the nitromethane molecule has led to the nitro elimination reaction.…”
Section: Introductionmentioning
confidence: 99%